Verification of the usefulness for short increment sensitivity index (SISI) test in determining bone conduction thresholds - K, Narendiran (Journal of All India Institute of Speech and Hearing)
Swisher, Stephens and Doehring (1966) suggested that the SISI test might be interpreted: as an indirect measure of bone conduction thresholds. Swisher et al (1966) also showed that normal and non-adapting sensorineural impaired ears discriminated a signal of 1 dB or less equally well at equivalent SPL. The study by Young and Harbert (1967) showed that at SPL’s of 45 and above every normal subject showed a SISI score of 65 per cent or higher for all frequencies. In general, a high SISI score occurs when at least 60 dB SPL reaches the inner ear. Sound pressure level (SPL) reaching the inner ear is the ;determining factor in the perception of 1 dB increments (Young and Harbert, 1967; Harbert, Young and Weiss, 1969; Martin and Salas, 1970 ).